KARAKTER VISUAL KORIDOR KAWASAN LAMA SEKANAK - PALEMBANG (Kasus: Jl. Depaten Baru â Jl. Ki Gede Ing Suro, Sekanak â Palembang) - , Hendi Warlika Sedo Putra, ST; , Ir. Ahmad Sarwadi, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Indonesia has many old cities scattered throughout the area. Those cities, formed from the old area with unique characteristics that became the forerunner to the development of a city. Characteristic structure formed by a group of artifacts / buildings with a value, history, culture, arts and sciences can be observed as a distinctive visual character. The specificity is important to maintainedas identity from one location separately to another location. Efforts in keeping the identity of a area faced with the fact that each city or area will experience growth. Without the "control" in the development, it would be difficult to maintain the visual character of the area formedbefore. This study describes the visual character of the old district Sekanak - Palembang, particularly Depaten baru street - Ki Gede Ing Suro street. This corridor is one of the old district with the unique and diverse architectural and development has occurred along the way. Therefore, the study was conducted to find out: (1) What kind of visual character that is formed along the corridor (2) what kind visual character Elements may be a bond of unity visual corridor (3) Provide design direction that could be used as a development reference to maintain and improve the visual character of the corridor. The method is by observing the physical elements forming the character through the observation of the longitudinal "views" and transverse "space" corridor, and do clacification of the building to explain the visual character that has formed along the corridor study. The results of this study indicate that development occurs along the corridor with the construction of new buildings have destroyed the old order which led to the loss unity of visual character, from